A study on the factors that influence training effectiveness / Norhayati Ramli - Ramli, Norhayati (Faculty of Business and Management, 2009)
The purpose of this study is to identify the dominant factor that contributes to the training effectiveness in Institute of Management Melaka (IMM). This study also examined the relationship between factors that influence training efficiency with learning outcome. The factors consist of trainer’s competency, training design as well as training method. Whether these factors are correlated with the learning outcome which consists of trainee’s knowledge acquisition as well as knowledge applies or not is tested in this study. In order to get the data, a total of 100 respondents involved to answer the questionnaire. Questionnaire used in this study are modified from previous study. Questionnaires are used to examine the relationship between dependent and independent variable in this research study. The model of this study is introduced by Ai-Yee Ooi, Syin-Hau Lee and Bryan Ching-Wing Lo. Furthermore, in order to analyse the data collected, Statistical Package of Social Science (SPSS) version14.0 has been used. The method of analysis consists of the highest mean score, frequency, as well as correlation has been used in this study. The study has found that the leading factor was training method based on the highest mean score. Besides, overall there has positive relationship with moderate significant level based on the correlation test.